Acinetobacter baumannii under Acidic Conditions Induces Colistin Resistance through PmrAB Activation and Lipid A Modification - Seo-Yeon Ko; Nayeong Kim; Seong-Yong Park; Seong-Yeop Kim; Minsang Shin; Je-Chul Lee (Antibiotics, 2023)
Colistin is a last-resort antimicrobial agent for treating carbapenem-resistant Acinetobacter baumannii infections. The activation of PmrAB by several environmental signals induces colistin resistance in Gram-negative bacteria. This study investigated the molecular mechanisms of colistin resistance in A. baumannii under acidic conditions using wild-type (WT) A. baumannii 17978, ΔpmrA and ΔpmrB mutants, and pmrA-complemented strains. The pmrA or pmrB deletion did not affect the growth of A. baumannii under acidic or aerobic conditions. A. baumannii under acidic (pH 5.5) and high-iron (1 mM) conditions showed 32- and 8-fold increases in the minimum inhibitory concentrations (MICs) of colistin, respectively. The ΔpmrA and ΔpmrB mutants at pH 5.5 showed a significant decrease in colistin MICs compared to the WT strain at pH 5.5. No difference in colistin MICs was observed between WT and mutant strains under high-iron conditions. The pmrCAB expression significantly increased in the WT strain at pH 5.5 compared to the WT strain at pH 7.0. The pmrC expression significantly decreased in two mutant strains at pH 5.5 compared to the WT strain at pH 5.5. The PmrA protein was expressed in the ΔpmrA strain carrying ppmrA_FLAG plasmids at pH 5.5 but not at pH 7.0. Lipid A modification by the addition of phosphoethanolamine was observed in the WT strain at pH 5.5. In conclusion, this study demonstrated that A. baumannii under acidic conditions induces colistin resistance via the activation of pmrCAB operon and subsequent lipid A modification.